2013
DOI: 10.21608/scvmj.2013.78285
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of heritabilities, genetic correlations, phenotypic correlations and genetic trends for production and reproduction traits of Holstein-Friesian dairy cattle using sire model

Abstract: A total of 3460 lactation records that represented 1059 dairy Holstein-Friesian cows were used in the present study that aimed to estimate genetic parameters such as heritability, genetic correlations, phenotypic correlations and genetic trends for some productive and reproductive traits. Studied traits were total milk yield, days in milk, fat %, protein %, dry period, age at first calving, number of services per conception, days open and calving interval. Data were collected from Egyptian Copenhagen Company i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
3
8
1
Order By: Relevance
“…was 0.002 . These results disagree with the finding of (Ghiasi et al 2011) and (Osman et al 2013) (Table.3) who found the heritability of services per conception within the range from 0.02 to 0.08. The results indicate that genetic improvement of these traits can be achieved through selection for these traits in breeding programs.…”
Section: Genetic Parameters Estimates Of Heritabilitycontrasting
confidence: 99%
See 2 more Smart Citations
“…was 0.002 . These results disagree with the finding of (Ghiasi et al 2011) and (Osman et al 2013) (Table.3) who found the heritability of services per conception within the range from 0.02 to 0.08. The results indicate that genetic improvement of these traits can be achieved through selection for these traits in breeding programs.…”
Section: Genetic Parameters Estimates Of Heritabilitycontrasting
confidence: 99%
“…The average number of services per conception (NSC was 1.7 this values is similar to (Ihlam et al 2012) was found to be 1.9 .Mean of NSC found is less than a study by (Osman et al 2013) estimate were 2 in the first lactation while 3.5 on the second lactation.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In parallel, Hammoud et al, (2014) reported the genetic and phenotypic correlation at low, medium and high level milk production between CI, 305-DMY was (r g =0.48, r p =0.70), (r g =0.82, r p =0.06) and (r g =0.75, r p =0.20), respectively. Additionally, Osman et al, (2013b) clarified positive genetic and phenotypic correlations in Holstein cows at the first parity between DO and LP (r g =0.990, r p =0.771) and positive correlations at the second parity were observed between LP and DO (r g =0.298, r p =0.544). The genetic and phenotypic correlation between LP and DO were positive (r g =0.037, r p = 0.406); 305-DMY and LP were positive (r g =0.037 and r p = 0.406) and 305-DMY and DO (r g = -0.005 and r p = 0.413) as mentioned by Faid Allah (2015).…”
Section: Descriptive Statisticsmentioning
confidence: 79%
“…Osman et al, (2013a) conducted heritability estimates of calving interval were 0.18 for second lactation at his studio on Holstein-Friesian dairy cattle. El-Shalamani (2011) reported heritability estimate of DO was 0.42 and Hammoud (2013) showed the values of DO was 0.48 for first lactation Holstein cows and Osman et al, (2013b) conducted heritability estimates at first parity of DO was 0.313 for Holstein cows and at second parity was 0.117. The difference in heritability estimates among various studies for the same trait could be attributed to differences in the number of records used, the correction for different non-genetic factors, the model used and the methodology used for estimation (Abou-Bakr, 2009).…”
Section: Descriptive Statisticsmentioning
confidence: 99%